Derivational Suffixes in Reading Texts of Higher Educational English Textbook - Nurliana Nurliana (Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to analyze the types of derivational suffixes used in reading texts of the higher educational English textbook. This research employed qualitative research, specifically content analysis, as the research design. The data involved derivational suffixes found in 15 reading texts of the higher educational English textbook English for Islamic Studies, used by the al-Qur’an and Tafsir Sciences study program students at IAIN Palangka Raya. The data collected were analyzed systematically. This research indicated four types of derivational suffixes in the reading texts of the higher educational English textbook: nominal, adjectival, adverbial, and verbal. Nominal suffixes were the most frequently used derivational suffixes in the reading texts of the higher educational English textbook. The research findings implied that the types of derivational suffixes frequently occurring in higher educational English textbook reading texts should be emphasized more in teaching reading comprehension.